Annealing-induced abnormal hardening in a cold rolled CrMnFeCoNi high entropy alloy. (15th March 2019) - Gu, Ji; Song, Min
Abstract: A CrMnFeCoNi equiatomic high entropy alloy (HEA) with a single solid solution was cold rolled, followed by annealing treatment. Annealing-induced abnormal hardening was observed for cold rolled alloy after annealing treatment at 773 K. Detailed microstructural characterizations indicated that the abnormal hardening phenomenon is not due to the precipitation hardening, but is attributed to the formation of long-range ordered structure in the HEA matrix. After a long time annealing at 773 K, the formations of nano-grains with sharp grain boundaries can be observed, and the reduced dislocation density and grain boundary relaxation also contribute to the hardening. Graphical abstract: Unlabelled Image